Physical Means and Trading Network of Onrust in the 17th and 18th Centuries - Yazril Azkar, Razaan; Wijaya, Daya Negri (Yupa: Historical Studies Journal, 2024)
This research aims to examine the physical facilities and trade networks on Onrust Island in the 17th-18th centuries. Onrust Island is a small island located in Batavia Bay (Jakarta) and has an important role in the history of trade in the Dutch East Indies. This research uses historical research methods through heuristics, source criticism, interpretation, and historiography. The research results show that Onrust has adequate physical facilities to support VOC trading operations, such as shipyards, warehouses, and commodity processing facilities. In the 17th century, Onrust also became Batavia's first defense center. In the 18th century, ship repair activities at Onrust began to decline due to the VOC's financial difficulties. However, Onrust remained an important post in the VOC trade network in the archipelago. This island became a stopover for the VOC trade fleet from various ports in Java and its surroundings. Products such as spices, wood, salt and others stopped at Onrust before being distributed further by the VOC. Thus, Onrust played an integral role in the VOC's maritime trade network in the archipelago in the 17th and 18th centuries through the infrastructure and logistics support it provided.